(untitled) (Training and Practice : Journal of Educational Sciences, 2007)
The development of agronomy to an independent scientific subject and the ceasing of feudal bounds were preconditions of the organization of the agricultural educational systems. The media of the results of scientific works from the turn of the 18th and 19th centuries were the educational institutes, societies, cooperations, books and journals. The usage of scientific results in practice was first propagated by „the rationalist school” founded by Albrecht Daniel Thaer. It had a principle role in the development of agricultural economics and its growth to an independent subject. The agricultural knowledge was mainly spread by cameralist departments in the beginning of 19th century, but during the century more and more agricultural academies were founded. Governmental funding was started during the middle of the 19th century, and it made possible the organisation of primary and secondary levels of a multi-level agricultural training system. The agricultural development happened in different times in the European countries. Apart from technical factors (estate and capital), the training systems, the societies, co-operation and knowledge meant a new uplifting power for the development of agriculture, as a utilization of rationalism. At the same time they raised the quality of agricultural work.